Teaching to make stone tools: new experimental evidence supporting a technological hypothesis for the origins of language. Issue 1 (December 2017) - Lombao, D.; Guardiola, M.; Mosquera, M.
Abstract The relationship between lithic technology, learning and language is a topic of growing interest in human evolution studies, and has therefore been the subject of numerous scientific papers in recent years. To evaluate the role of language in the social transmission of lithic technology, we designed and developed an experimental protocol through which we compared the acquisition of knapping skills in thirty non-experts in the early stages of learning, by means of three mechanisms of social transmission: imitation-emulation, gestural communication, and verbal communication. All the apprentice knappers carried out the experimental task with blanks that were equal in shape and size, and were requested to replicate what the expert knapper was doing: the alternating method, a sufficiently simple, but systematic technique for detaching flakes from a core. We analysed each participant's actions, including those of the master knapper, the final products (flakes and cores), and the knapping sequences, by analysing the refits. Our results show that the apprentices improved their knapping skills in teaching conditions -both gestural and verbal communication-, and specially through the latter. In conclusion, our study supports the hypothesis of co-evolution between lithic technology and social learning, which could have favoured the emergence of verbal language.